1987
DOI: 10.1038/bjc.1987.200
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second primary tumours among childhood cancer survivors

Abstract: Summary Among a cohort of 10,106 three-year survivors of childhood cancer, 90 second primary tumours (SPTs) were observed. Within 25 years of 3-year survival about 4% developed a SPT, about 6-fold expected, the relative risk not varying much with increasing follow-up.Following genetic retinoblastoma we observed 30-fold the expected number of SPTs, and over 400-fold the expected number of osteosarcomas. The risk of SPT in the absence of radiotherapy and chemotherapy (inherent risk) following genetic retinoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
134
1
4

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 317 publications
(152 citation statements)
references
References 23 publications
13
134
1
4
Order By: Relevance
“…The well-recognised increased risk of a second malignant neoplasm (SMN) (Meadows et al, 1985) may represent the greatest challenge to long-term survival (Robison and Mertens, 1993). Further study of their causes, which include both exposure to chemotherapy (CT), radiotherapy (RT) and genetic predisposition (Kony et al, 1997), requires follow-up of large numbers of survivors with a wide spectrum of treatments.Soft tissue sarcoma (STS) represents an important risk of SMN following childhood cancer, particularly heritable retinoblastoma (Draper et al, 1986;Hawkins et al, 1987;Westermeier et al, 1998; Menu-Branthomme et al, 2004). The one published case -control study of STS following childhood cancer demonstrated an independent association with exposure to RT and CT with procarbazine (Menu-Branthomme et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The well-recognised increased risk of a second malignant neoplasm (SMN) (Meadows et al, 1985) may represent the greatest challenge to long-term survival (Robison and Mertens, 1993). Further study of their causes, which include both exposure to chemotherapy (CT), radiotherapy (RT) and genetic predisposition (Kony et al, 1997), requires follow-up of large numbers of survivors with a wide spectrum of treatments.Soft tissue sarcoma (STS) represents an important risk of SMN following childhood cancer, particularly heritable retinoblastoma (Draper et al, 1986;Hawkins et al, 1987;Westermeier et al, 1998; Menu-Branthomme et al, 2004). The one published case -control study of STS following childhood cancer demonstrated an independent association with exposure to RT and CT with procarbazine (Menu-Branthomme et al, 2004).…”
mentioning
confidence: 99%
“…Soft tissue sarcoma (STS) represents an important risk of SMN following childhood cancer, particularly heritable retinoblastoma (Draper et al, 1986;Hawkins et al, 1987;Westermeier et al, 1998; Menu-Branthomme et al, 2004). The one published case -control study of STS following childhood cancer demonstrated an independent association with exposure to RT and CT with procarbazine (Menu-Branthomme et al, 2004).…”
mentioning
confidence: 99%
“…Abramson et al (1984), we have not included them as second tumour cases as in our opinion the intracranial lesion in these cases is not histologically distinct from the primary retinoblastoma. Further details of the ascertainment of cases will be given by Hawkins et al (1987).…”
Section: Methodsmentioning
confidence: 99%
“…In this report we describe 161 patients who have developed more than one primary neoplasm and examine the various factors which may have influenced the development of the second primary tumour. We have not attempted to estimate the risk of developing a second tumour in this paper as an analysis of incidence rates is the subject of a separate communication (Hawkins et al, 1987). Our main purpose here is to describe the patterns of multiple tumours that have been observed and to identify the possible influence of genetic factors and previous therapy in the pathogenesis of the second tumour.…”
mentioning
confidence: 99%
See 1 more Smart Citation